L’éthique du care dans le champ éducatif ou le nouveau paradigme de la bienveillance - Corinne Roux-Lafay (Éducation et Socialisation, 2016)
The care ethic is based on the attention paid to a subject’s original character in his or her constitutive vulnerability. It is at the heart of current reforms to French schools and involves questioning of the teacher’s stance and the pupil’s status. A teacher’s moral stance is one of exemplarity with no emotional interference which still needs a benevolent attitude which we may call concern. From the pupil’s side, in relation with the new programmes, the idea is to develop relational skills which are part of care itself in such a way as to recognize its importance in teaching pupils. However this paradigm reconfigures the Ecole de la Republique, the French schools system, which is historically constructed on a foundation of rationality which suppresses otherness and therefore